Natural Sequential Collapse Method: A Common Technique to Identify the Intersegmental Plane - Deng, Yuanlin; Luo, Yilin; Zhang, Min; Ge, Mingjian (The Thoracic and Cardiovascular Surgeon, 2024)
The natural sequential collapse method (NSCM) can be employed during surgery to reduce the duration of segmentectomy. This method avoids inflating the lung by rapidly blocking vessels within the tumor basin. It is important to note that the color of the lungs should be used to determine the surgical procedure. The NSCM is efficient and straightforward in revealing the intersegmental plane.
Keywords: thoracoscopy/VATS; lung cancer treatment (surgery; medical); tumor